The Historiography Review of Problem of Settling and Development of Real Schools in Ukraine (1872 -1917) - Halyna Bondarenko (Pedagogical Discourse, 2013)
In the article the historiography review of problem of settling and development of the real schools in Ukraine (1872 - 1917) is examined. The author lights up basic questions, which touch the analysis of literary base of settling and development of the real schools in Ukraine. Literary sources, written by the eyewitnesses of events of the noted period, are analyzed in the publication; editions of soviet period are examined, researches of contemporary scholars are characterized in relation to this theme. On the basis of literary searches, attitude of researchers of different periods is determined toward the problem of development of secondary education of the second half of the 19th century - beginning of 20th century on the whole, and real education - in particular.